1987
DOI: 10.1093/cvr/21.12.902
|View full text |Cite
|
Sign up to set email alerts
|

Nature and pressure dependence of damage induced by distension of human saphenous vein coronary artery bypass grafts

Abstract: Surgical preparation of human saphenous vein for coronary artery bypass grafting involving distension and storage in iso-osmotic sodium chloride solution reduced tissue adenosine triphosphate (ATP) (mean(SEM] concentration from 280(20) nmol.g-1 wet wt (n = 25) to 140(30) nmol.g-1 wet wt (n = 12) and the adenosine triphosphate to adenosine diphosphate (ATP:ADP) concentration ratio from 2.4(0.1) to 1.2(0.2). Since removal of endothelium from freshly isolated vein did not affect ATP concentration or ATP:ADP ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 0 publications
0
44
1
2
Order By: Relevance
“…Preparation of the veins before implantation is associated with a limited loss of endothelial cells, in contrast with the findings of Angelini et al (1987Angelini et al ( , 1989, who reported a much higher endothelial cell loss. However, they estimated the endothelial cell loss after a pharmacological experiment and used a different preparation technique.…”
Section: Discussioncontrasting
confidence: 64%
“…Preparation of the veins before implantation is associated with a limited loss of endothelial cells, in contrast with the findings of Angelini et al (1987Angelini et al ( , 1989, who reported a much higher endothelial cell loss. However, they estimated the endothelial cell loss after a pharmacological experiment and used a different preparation technique.…”
Section: Discussioncontrasting
confidence: 64%
“…22 This type of distension has been shown to cause morphological and biochemical alterations in the vessel wall. 23,24 In addition, several hemodynamic changes occur in the SV after implantation into the coronary circulation, including alterations in blood flow, transmural pressure, shear stress, and radial stress. 25 In addition, interruption of the vasa vasorum during explantation of vein is likely to cause ischemic necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the level of intimal hyperplasia is directly linked to the degree of endothelial denudation, which, in vein grafts is caused by luminal distension during surgery, ischemia, damage at surgical anastomoses and continued physical trauma under arterial conditions (2)(3)(4). Moreover arterial tangential pressure, medial damage and thickening as well as shear stress changes and altered fl ow patterns are involved in the development of intimal hyperplasia (5)(6)(7).…”
mentioning
confidence: 99%